Invited paper: Bridging EDA and silicon photonics design: enabling robust-by-design photonic integrated circuits - Ghanaatian, Zahra, author; Mirza, Asif, author; Shafiee, Amin, author; Pasricha, Sudeep, author; Nikdast, Mahdi, author; ACM, publisher (Colorado State University. Libraries, 2025)
Silicon photonic devices are essential components of integrated optical communication systems and emerging photonic processors. However, their performance is notably impacted by fabrication-process variations (FPVs), which primarily stem from optical lithography imperfections. The impact of FPVs can accumulate and deteriorate the system-level performance through, for example, increasing system power consumption, accumulated crosstalk noise, and degrading signal integrity in photonic systems. In this paper, we discuss the promise of variation-aware design-space exploration and optimization to enhance photonic device robustness under different FPVs while considering two silicon photonic devices used widely in different applications, namely Microring Resonators (MRRs) and Mach-Zehnder Interferometers (MZIs). In addition, we consider a system-level case study of an MZI-based coherent neural network, where we show how our proposed variation-aware design optimization at the device level helps improve the network accuracy by up to 88% under FPVs.
Bridging EDA and silicon photonics design: enabling robust-by-design photonic integrated circuits
Keywords: silicon photonics; fabrication-process variations; microring resonators; Mach Zehnder interferometers; design exploration; design automation and optimization